Coma state and the electroencephalogram burst-suppression pattern related to baclofen overdose. - Escobar-Montalvo, Juan (2019)
Baclofen is a structural analog of gamma-aminobutyric acid, primarily used as a skeletal muscle relaxant for treatment of spasticity and dystonia. The clinical picture of baclofen intoxication includes reduction or loss of consciousness and manifestations such as sleepness, coma or even death. Electroencephalograms performed in these cases have consistently shown the so-called burst-suppression pattern. The case of a female patient who suddenly presented difficulty to still-standing and mutism and later evolved into coma, is presented. A detailed study was performed in the emergency department, including an electroencephalogram compatible with a continuous burst-suppression pattern. The patient was treated with dialysis in the face of a possible baclofen intoxication and, in a period of five days, the clinical symptoms reverted and the electroencephalographic activity was normalized.